Hester Prynne and Ethan Frome: Two Faces of the Same Tragedy - Al-Kurwy, Hind Ahmed; Kadhem, Suhaib Majeed (الجامعة المستنصرية - كلية التربية الأساسية, 2017)
تتميز المأساة الإنسانية باستمراريتها على مدى التاريخ الإنساني ولقد قدم العديد من الكتاب أفكارهم المتعلقة بالمأساة في مختلف العصور حيث يقدم كل كاتب نظرته الشخصية عن المعاناة الإنسانية. تسلط الدراسة الحالية الضوء على هذا الموضوع من خلال إجراء المقارنة بين روايتين الأولى هي للكاتب ناثنيال هاوثورن (الحرف القرمزي) والأخرى للكاتبة إديث هوارتون (إيثان فروم) من خلال إجراء مقارنة بين كل من النصين وكيفية معالجة موضوع المأساة الإنسانية في كل منهما.
Human tragedy is characterized by its continuity over and over in human history. Many writers elaborate different tragedies, each according his\her own experience and understanding of world tragedies. The present study shows a comparison of such tragedies between two novels; one by Nathaniel Hawthorne's Scarlet Letter and the other by Edith Wharton's Ethan From. The study sheds light on the way each novelist presents different sorts of human agony, the points they meet and the points they differ.
Keywords: الأدب الإنجليزي -- الماساة الإنسانية -- السرد الروائي -- لنقد الأدبي